2020
DOI: 10.1515/dmdi-2020-0136
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 in the light of epidemic disease described in Unani medicine

Abstract: Unani system of medicine is based on the humoral theory postulated by Hippocrates, according to him the state of body health and disease are regulated by qualitative and quantitative equilibrium of four humours. Amraz-e-Waba is an umbrella term which is used in Unani medicine for all types of epidemics (smallpox, measles, plague, Hameer Saifi, influenza, Nipaha, Ebola, Zika, and 2019 novel coronavirus, etc.) mostly fatal in nature. The coronavirus disease 2019 (COVID-19) is a severe acute respiratory infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Traditional applications of saffron range from treating skin or metabolic conditions (such as erysipelas and diabetes in traditional Iranian medicine or acne in traditional Greek medicine to sexual dysfunction, as saffron is believed to possess aphrodisiac properties [ [14] , [15] , [16] ]. Saffron historically makes up part of both the Unani Medicine, which used saffron as an antidote during periods of Amraz-e-Waba (a term applied to denote rather fatal epidemics) [ 17 ], and Persian Medicine. Of note, textual searches for compounds with potential actions against respiratory diseases have increased in light of the COVID-19 [ 18 ].…”
Section: Overview Of Saffron and Its Biological Activitiesmentioning
confidence: 99%
“…Traditional applications of saffron range from treating skin or metabolic conditions (such as erysipelas and diabetes in traditional Iranian medicine or acne in traditional Greek medicine to sexual dysfunction, as saffron is believed to possess aphrodisiac properties [ [14] , [15] , [16] ]. Saffron historically makes up part of both the Unani Medicine, which used saffron as an antidote during periods of Amraz-e-Waba (a term applied to denote rather fatal epidemics) [ 17 ], and Persian Medicine. Of note, textual searches for compounds with potential actions against respiratory diseases have increased in light of the COVID-19 [ 18 ].…”
Section: Overview Of Saffron and Its Biological Activitiesmentioning
confidence: 99%
“…The main symptoms of COVID-19 are fever, cough, fatigue, slight dyspnoea, sore throat, headache, conjunctivitis, and gastrointestinal issues [18] . Severe disease and death are more likely to occur in the elderly, and probably in those with preexisting chronic conditions such as diabetes, malignancies of cardiovascular disease, and hypothyroidism [19,20,21] .…”
Section: Symptomsmentioning
confidence: 99%
“…Medical practitioners like Hippocrates and Pliny have used it, and famous women like Cleopatra made its use in cosmetics (Husaini, 2010). Many in vitro and in vivo studies have confirmed the saffron as an antiviral, antioxidant, bronchodilator, anti-inflammatory, and strong immune booster acting on humoral as well as cellular immunity (Bhat et al, 2020;Kadri, 2014;Alam et al, 2020;Alshehri et al, 2017;Chiavaroli et al, 2017;Shahbazi and Bolhassani, 2016).…”
Section: Introductionmentioning
confidence: 97%